Pengaruh Sistem Kerja Kontrak, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Politeknik Penerbangan Surabaya - Rahma Oktaviani Dewi; Hadi Sunaryo; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine : 1) Description of employee performance, contract work system, work motivation and work environment, 2) Effect of contract work systems, work motivation and work environment on employee performance, 3) Effect of contract work systems on employee performance, 4) The influence of work motivation on employee performance, 5) The influence of the work environment on employee performanceThe method used in this research is a quantitative research method with a descriptive approach and is carried out at the Surabaya Aviation Polytechnic with a population of 57 contract employees. The data collection technique used a questionnaire with measurements using a Likert scale. The data analysis technique used was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis F test, hypothesis t test and coefficient of determination.The results of this study indicate that: 1) The contract work system, work motivation and work environment have a significant effect on employee performance, 2) The contract work system has a significant effect on employee performance, 3) Work motivation has a significant effect on employee performance, 4) The work environment has a significant effect. on employee performance. Keywords:  Contract Work System, Work Motivation, Work Environment, Employee Performance.